Meningeal lymphatic vessel dysfunction exacerbates brain injury in CVST mice via endoplasmic reticulum and oxidative stress pathways - Ying, Jianbin; Li, Jun; Wu, Xianqun; Chen, Xuanjie; Zhang, Hao; Wei, Liangfeng; Jing, Junjie; Wang, Shousen (Frontiers in Immunology, 2026)
ObjectiveMeningeal lymphatic vessels (mLVs) play a significant role in neurological homeostasis and disease. However, their contribution to brain injury following cerebral venous sinus thrombosis (CVST) remains unknown. This study investigated whether mLV dysfunction influences the pathological progression of CVST by regulating the endoplasmic reticulum (ER) and oxidative stress(OS)pathways.MethodA total of 65 male C57BL/6J mice were randomly assigned to four groups: sham-operated, CVST; CVST combined with cervical lymph node ligation (CVST + Ligation); and 4-phenylbutyric acid (4-PBA) intervention. The CVST model was established by inducing thrombosis in the superior sagittal sinus. All sample collection and experimental assays were performed at 2 days post-modeling. Neurobehavioral assessment, histopathological staining, immunofluorescence, western blotting, reverse transcription quantitative polymerase chain reaction, enzyme-linked immunosorbent assay, and bioinformatics analyses were employed to comprehensively evaluate neurological function, brain injury, inflammatory response, key molecular expression in ER/oxidative stress pathways, and alterations in related signaling pathways following mLV dysfunction.ResultCompared to the CVST group, mice in the CVST+Ligation group exhibited more severe neurological deficits, aggravated histopathological brain injury, increased neuronal loss, and enhanced cellular apoptosis. Transcriptomic analysis following lymphatic dysfunction revealed significant enrichment of pathways related to inflammatory response, cytokine-cytokine receptor interaction, and endoplasmic reticulum (ER) stress. At the levels of immunofluorescence, ELISA, Western blot, and mRNA expression, lymphatic ligation significantly upregulated markers of ER stress and microglial activation/apoptosis (including GRP78, CHOP, ATF4, p-eIF2α, NLRP3, and IL-1β) (P < 0.05), as well as downstream apoptosis-related proteins (such as PUMA and Caspase-12) (P < 0.05). It also promoted the release of pro-inflammatory cytokines (IL-6, IL-1β, TNF-α, and IL-17) (P < 0.05). Administration of the ER stress inhibitor 4-PBA effectively reversed these molecular alterations and significantly alleviated brain injury and neuroinflammation in CVST+Ligation mice.ConclusionDysfunction of mLVs exacerbates brain injury after CVST by promoting neuroinflammation via the ER and oxidative stress pathways. Therapeutically targeting mLVs may represent promising strategies for managing CVST-related neurological injury.